Association of the triglyceride-glucose index and vascular target organ damage in a Beijing community-based population - Ji, Wenjun; Gao, Lan; Sun, Pengfei; Jia, Jia; Li, Jianping; Wang, Xingang; Fan, Fangfang; Zhang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Objective We aimed to explore the association between the triglyceride-glucose (TyG) index, a marker of insulin resistance (IR), and vascular target organ damage (TOD) in a Beijing community-based population, China. Methods A total of 6,015 participants from an atherosclerosis cohort survey performed in the Shijingshan District in Beijing, China were included in our analysis. Vascular TOD, such as carotid-femoral pulse wave velocity (cfPWV), brachial-ankle pulse wave velocity (baPWV), and the urine albumin-to-creatinine ratio (UACR) were all evaluated. Results The overall mean age of all the participants was 62.35 years, 3,951 (65.69%) were female, and mean TyG index was 8.81. In univariable regression analyzes, an increased TyG index was associated with higher cfPWV, baPWV, lnUACR, and higher risk of cfPWV ≥ 10 m/s, baPWV ≥ 1,800 cm/s, and UACR ≥ 30 mg/g, respectively. Multivariable regression analyzes showed subjects with the TyG index in top tertile had a significant increase in cfPWV (β = 0.29 m/s; 95% confidence interval [95% CI] 0.19–0.40; pfortrend < 0.001), baPWV (β = 69.28 cm/s; 95% CI 50.97–87.59; pfortrend < 0.001), lnUACR (β = 0.23; 95% CI 0.13–0.34; pfortrend < 0.001), and had a higher risk of cfPWV ≥ 10 m/s (odds ratio [OR] = 1.47; 95% CI 1.17–1.85; pfortrend < 0.001), baPWV ≥ 1,800 cm/s (OR = 1.79; 95% CI 1.48–2.17; pfortrend < 0.001), and UACR ≥ 30 mg/g (OR = 1.71; 95% CI 1.30–2.24; pfortrend < 0.001) after fully adjusting for age, sex, body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), estimated glomerular filtration rate (eGFR), self-reported coronary heart disease (CHD) and stroke, antihypertensive drugs, hypoglycemic drugs, and lipid-lowering drugs. Consistent conclusions were obtained in the subgroups without hypoglycemic and lipid-lowering medications or aged younger than 65 years old. Conclusions The TyG index was positively associated with artery stiffness and nephric microvascular damage in a Beijing community-based population in China. This result provides evidence that the TyG index may serve as a simple and effective indicator to reflect vascular TOD.